2004
DOI: 10.1105/tpc.019802
|View full text |Cite
|
Sign up to set email alerts
|

Jittery, a Mutator Distant Relative with a Paradoxical Mobile Behavior: Excision without Reinsertion

Abstract: The unstable mutation bz-m039 arose in a maize (Zea mays) stock that originated from a plant infected with barley stripe mosaic virus. The instability of the mutation is caused by a 3.9-kb mobile element that has been named Jittery (Jit). Jit has terminal inverted repeats (TIRs) of 181 bp, causes a 9-bp direct duplication of the target site, and appears to excise autonomously. It is predicted to encode a single 709-amino acid protein, JITA, which is distantly related to the MURA transposase protein of the Muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 57 publications
4
70
0
Order By: Relevance
“…Here, we demonstrate that, regardless of the source of transposase tested, excision of mPing is usually precise. As such, this is only the second characterized plant transposon with a preference for precise excision (22). Our data also indicate that mPing, unlike most (but not all) DNA transposons, does not have a preference for insertion into sites linked to the donor.…”
Section: Discussionmentioning
confidence: 54%
“…Here, we demonstrate that, regardless of the source of transposase tested, excision of mPing is usually precise. As such, this is only the second characterized plant transposon with a preference for precise excision (22). Our data also indicate that mPing, unlike most (but not all) DNA transposons, does not have a preference for insertion into sites linked to the donor.…”
Section: Discussionmentioning
confidence: 54%
“…While previous studies identified two major groups of plant MULEs (MuDR and Jittery-like) (Lisch 2002;Xu et al 2004), we were surprised to find a third lineage in L. japonicus ( Figure 3A). In addition to MuDRlike (27 elements) and Jittery-like (24 elements) MULEs, the third lineage is most closely related to a small group of recently discovered fungal MULEs called Hop from Fusarium oxysporum (Chalvet et al 2003) and to a MULE element from Magnaporthe grisea than to any other plant element.…”
Section: Te Abundancementioning
confidence: 56%
“…A new MULE lineage: Virtually all MULEs identified to date in plants belong to one of two groups: MUDR and Jittery-like (Yu et al 2000;Lisch 2002;Xu et al 2004). It was therefore surprising to find a third group of MULEs in L. japonicus that is more closely related to the fungal element Hop (Chalvet et al 2003) than to MUDR or Jittery-like MULEs ( Figure 3A).…”
Section: Copia-like Elements Containing An Extra Orfmentioning
confidence: 93%
“…Most of MULE transposases in plants were reported to exhibit higher similarity to the transposase of Jittery than to MURA (Walbot and Rudenko 2002;Xu et al 2004) and the Jittery clade also included the largest numbers of MULEs in T. aestivum. Many MULE transposases belonging to the Jittery clade are probably also present in T. urartu.…”
Section: Discussionmentioning
confidence: 99%
“…Homologous sequences from Triticum and Aegilops were searched in the TIGR Wheat Genome Database using BLASTn and tBLASTx (Altschul et al 1997). Two other Mutator-related elements, Trap (Comelli et al 1999) and Jittery (Xu et al 2004), have been identified in maize. Mutator-like transposases were divided into four classes in sugarcane, rice and Arabidopsis (Rossi et al 2004).…”
Section: Sequence Analysesmentioning
confidence: 99%